Intestinal Tuberculsis - 5 years experience in Tertiary Care Hospital (Medical Forum Monthly, 2024)
Background; Abdominal tuberculosis (TB) is a common disease in developing countries and reemerging in the west. This disease is still diagnostic dilemma for physicians and surgeons, as it mimics many abdominal diseases.Objective: To evaluate the clinical presentation and management of abdominal tuberculosis in our set up.Study Design: prospective studyPlace and duration of Study: This study was conducted in surgical unit III, Peoples University of Medical & Health Sciences Hospital Nawabshah, from July 2006 to June 2011.Materials and methods: Total 70 patients were included in this study from 205 suspected cases. The cases were either previously diagnosed or diagnosed during operation performed for intestinal obstruction, peritonitis or appendicitis. Patients were confirmed on the basis of histopathology, cultures and AFB.Results: Age of the patients ranged between 6 to 38 years. Male to female ratio was 1.3:1. Abdominal pain and weight loss were the most common symptoms. Common presentation was intestinal obstruction and peritonitis. Majority of patients underwent resection and anastomosis and limited right hemicolectomy.Conclusion: It has been emerged from our study that abdominal TB presents with different clinical features which are nonspecific and often diagnosed during laparotomy. Majority of patients underwent resection and anastomosis and limited right hemicolectomy.